Representasi Feminisme: Analisis Semiotika Pada Film Mencuri Raden Saleh - Diandra Wike Riskia Salsabila (Jurnal Ilmu Komunikasi, 2021)
The issue of feminism is always an interesting topic to discuss. The development of feminism in Indonesia itself is relatively slow. This is because Indonesia is attached to eastern culture which prioritizes customs and manners, where as we know most of the customs in Indonesia place women below men. In addition, feminism is also considered contrary to religious values. However, currently feminism has slowly been recognized and implemented in Indonesia. We can see this through how the mass media depicts women. In the past, women were used as objects in the mass media, one of which was film. Usually women are depicted as weak, powerless, beautiful, graceful and seductive. Even a film is considered interesting if the main actor is a woman. However, nowadays there are many films that place women on an equal footing with men. Stealing Raden Saleh is one of the Indonesian films that will be broadcast in 2022 which provides an overview of gender equality between men and women which is fought for by feminists. The purpose of this research is to represent the meaning of the message of feminism in the film Mencuri Raden Saleh. The writer uses a qualitative method and chooses John Fiske's semiotic analysis approach to convey the code and meaning in the film. The results of the study show that the representation of gender equality that feminists are fighting for in the film Mencuri Raden Saleh has three stages according to John Fiske, namely the level of reality, the level of representation and the level of ideology.